Answer:
see explanation
Explanation:
(3)
The opposite sides of a parallelogram are congruent, so
6x = 3x + 15 ( subtract 3x from both sides )
3x = 15 ( divide both sides by 3 )
x = 5
and
2y - 10 = y + 5 ( subtract 5 from both sides )
y - 10 = 5 ( add 10 to both sides )
y = 15
Then x = 5 and y = 15
-------------------------------------------------------------------------
(4)
The diagonals of a parallelogram bisect each other, thus
y = 4x - 6 → (1)
9x - 25 = 2y → (2)
Substitute y = 4x - 6 into (2)
9x - 25 = 2(4x - 6)
9x - 25 = 8x - 12 ( subtract 8x from both sides )
x - 25 = - 12 ( add 25 to both sides )
x = 13
Substitute x = 13 into (1)
y = 4(13) - 6 = 52 - 6 = 46
Then x = 13 and y = 46